Energy efficiency investment in a developing economy: Financial development and debt status implication - Chukwunonso Ekesiobi; Stephen O. Ogwu; Joshua Chukwuma Onwe; Ogonna Ifebi; Precious Muhammed Emmanuel; Kingsley N. Ashibogwu (African Governance and Development Institute (AGDI), 2023)
Purpose: Our study assesses financial development and debt status impact on energy efficiency in Nigeria as a developing economy. Methodology: We combined the Autoregressive Distributed Lag (ARDL), FMOLS, and CCR analytical methods to estimate the parameters for energy efficiency policy recommendations. Secondary data between 1990 and 2020 were used for the analysis. Findings: The result confirms the long-run nexus between energy efficiency, financial development and total debt stock. Furthermore, the ARDL estimates for our key variables show that financial development promotes energy efficiency in the short run but hinders long-run energy efficiency. Total debt stock limits energy efficiency in Nigeria in short and long-run periods. Originality: The environmental consequences of energy intensity are being felt globally, with the developing countries most vulnerable. The cheapest way to curb these consequences is to promote energy efficiency to reduce the disastrous effect. Driving energy efficiency requires investment in energy-efficient technology, but the challenge for developing economies i.e. Nigeria's funding, remains challenging amid a blotted debt profile. This becomes crucial to investigate how financial sector development and debt management can accelerate energy-efficient investments in Nigeria. Practical Implication: The financial sector must ensure the availability of long-term credit facilities to clean energy investors. The government must maintain a sustainable debt profile to pave the way for capital expenditure on clean energy projects that promote energy efficiency. Limitation: The limitation of this study is that the scope is limited to Nigeria as a developing economy. The need to support energy efficiency projects is a global call requiring cross-country analysis. Despite our study focusing on Nigeria, it provides useful insights that can guide energy efficiency policy through the financial sector and debt management.
Keywords: E22; E44; E62; 330; Financial Development; Public Debt; Energy Efficiency; Environment; Nigeria